Reimagining Public Schools and Teacher Education: Solidarity and Activism through Testimonio - de Saxe, Jennifer Gale (My University, 2014)
Abstract This dissertation examines the interdisciplinary role that critical feminism and critical education may have in regards to reconceptualizing the way we understand the purposes of schooling. Through an examination of the historical and current debates regarding the purposes of schooling and teacher education, this dissertation offers another way to conceptualize a democratic and liberatory education. With the political and self-reflexive act of sharing ones educational experiences through testimonio, educators have the potential to make school a place that truly aims to embrace all of our students and their families. Further, by reconceptualizing the purpose of schooling as a place of democratic teaching and learning, educators can work and support students in becoming critical thinkers, local and global activists, as well as help their students understand the power they have in affecting the course of history. Therefore, by aiming to reframe and infuse our teacher education programs with elements of critical feminism, we can refocus the attention of teacher preparation and our understanding of the purposes of schools as places that put the human component of teaching and learning at the center.
Thesis (Ph.D.)--University of Washington, 2014
Keywords: Critical Education Theory; Critical Feminist Theory; Equity; Social Justice; Teacher Education; Testimonio; Education; Elementary education; Women's studies; education - seattle